2016
DOI: 10.3390/s16122151
|View full text |Cite
|
Sign up to set email alerts
|

Accelerometry-Based Activity Recognition and Assessment in Rheumatic and Musculoskeletal Diseases

Abstract: One of the important aspects to be considered in rheumatic and musculoskeletal diseases is the patient’s activity capacity (or performance), defined as the ability to perform a task. Currently, it is assessed by physicians or health professionals mainly by means of a patient-reported questionnaire, sometimes combined with the therapist’s judgment on performance-based tasks. This work introduces an approach to assess the activity capacity at home in a more objective, yet interpretable way. It offers a pilot stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 42 publications
0
11
0
Order By: Relevance
“…Nevertheless, patterns also contain inherent noise in the sense that parts of the movement are not defining aspects of a particular activity. Current results are promising for many subjects, but an earlier study on the Sensewear dataset showed that much is to be gained by combining pattern features with more general statistical features [47]. In the future, it could be beneficial to merge the feature set obtained by HODA with the statistical features employed there.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, patterns also contain inherent noise in the sense that parts of the movement are not defining aspects of a particular activity. Current results are promising for many subjects, but an earlier study on the Sensewear dataset showed that much is to be gained by combining pattern features with more general statistical features [47]. In the future, it could be beneficial to merge the feature set obtained by HODA with the statistical features employed there.…”
Section: Discussionmentioning
confidence: 99%
“…The dynamic regions of the signal are subsequently separated from the more static ones. This separation was implemented as a step-wise adaptive approach [47].…”
Section: Segment Identificationmentioning
confidence: 99%
“…The vest provides a portable and low-cost solution that can be used indoors and outdoors to provide long-term care at home. The recognition abilities of accelerometerbased detection and activity monitoring can help in assessing rheumatic and musculoskeletal diseases [7]. There are several other examples of similar research and development studies that are shifting the paradigm of patient care and welfare.…”
Section: Background Workmentioning
confidence: 99%
“…The vest provides a portable and low-cost solution that can be used indoors and outdoors to provide long-term care at home. The recognition abilities of accelerometer-based detection and activity monitoring can help in assessing rheumatic and musculoskeletal diseases [7]. There are several other examples of similar research and development studies that are shifting the paradigm of patient care and welfare.…”
Section: Background Workmentioning
confidence: 99%